A politica de inserção do Panama no mercado latino americano de serviços - Leon, Jaime Ernesto Hughes (1996)
The research we now present has the objective of identifying the fundamentaIs of the Panamanian Govemment policy for its definitive participation in the intemational trade of services and also verify the present contribution of the nation for its consolidation as a service supplier to the intemational trade between Latin America and the Caribbean and the rest of the world. The processes that have been observed and identified were analyzed taking into account theories of public policies and economical integration and development. The final conc1usion is that the policies adopted by the Republic of Panama and the development of its export service infra - structure identified in this study, have a meaningful importance in Panama's inc1usion in the new world order. These factors constitute in effective ways of promotion, propagation and strengthening of the nation image as a reliable supplier of intemational services.